2020
DOI: 10.3390/catal10030314
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitrate on the Sol-Gel Spread Self-Combustion Process and Its Effect on the NH3-SCR Activity of Magnetic Iron-Based Catalyst

Abstract: Sol-gel spread self-combustion is the burning of the complexing agent in dried gel and the oxidant. Meanwhile, high temperature takes place during the combustion process, which is harmful to the pore structure of the catalyst. The nitrate from metal nitrate precursors as an oxidant could participate in the spread of the self-combustion process. Therefore, the influence of nitrate from metal nitrate on the spread self-combustion of an iron–cerium–tungsten citric acid gel and its catalytic performance of NOx red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Addition of nitric acid (NO 3À ) increased the oxidizing environment and increased the rate of oxidation: NO 3À provides in-situ oxidizing atmosphere for the breakdown of organic matters and triggered the sol-gel to complete combustion process. [24,25] Finally, the dry gel starts to auto-combustion (high exothermic) for about 1-2 mins, after that the burnt gel was turned to crispy powder of SCSCOs.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of nitric acid (NO 3À ) increased the oxidizing environment and increased the rate of oxidation: NO 3À provides in-situ oxidizing atmosphere for the breakdown of organic matters and triggered the sol-gel to complete combustion process. [24,25] Finally, the dry gel starts to auto-combustion (high exothermic) for about 1-2 mins, after that the burnt gel was turned to crispy powder of SCSCOs.…”
Section: Resultsmentioning
confidence: 99%
“…The DSC graph reveals two peaks, one endothermic at 25 °C due to water loss and one exothermic at 300-375 °C due to metal nitrate combustion with urea. 31 As a result, the formation temperature of the studied sample was over 400 °C. As a consequence, the nano-sample was prepared at 500 °C.…”
Section: Thermal Analysesmentioning
confidence: 97%
“…Different from NRR, however, the products of NOR are nitrates rather than ammonia, which can not only provide nitrogen sources and nutrition for soil but also play a crucial role in numerous manufactures, for example, making gunpowder, curing coronary heart disease, and so on. 108,[112][113][114][115] It has been suggested that N 2 is oxidized to nitrate by the following two steps: the first step is to activate the N≡N triple-bond, converting the inert N 2 to active NO * intermediates ( * represents to active sites). The second step is a redox reaction, in which NO * is transformed into nitrate over the active sites.…”
Section: Nitrogen Oxidation Reactionmentioning
confidence: 99%
“…In addition to this route, nitrogen oxidation to nitrate (ie, NOR) has also been considered a feasible way to achieve the same goal of fixing nitrogen. Different from NRR, however, the products of NOR are nitrates rather than ammonia, which can not only provide nitrogen sources and nutrition for soil but also play a crucial role in numerous manufactures, for example, making gunpowder, curing coronary heart disease, and so on 108,112‐115 . It has been suggested that N 2 is oxidized to nitrate by the following two steps: the first step is to activate the N≡N triple‐bond, converting the inert N 2 to active NO * intermediates ( * represents to active sites).…”
Section: Conversion Between Nitrogen and Nitrogen Oxidesmentioning
confidence: 99%